Establishing an Effective Peer Support Program for Reading Remediation - T. Kilag, Osias Kit; B. Canubas, Ana Lissa; R. Uy, Lariz Mae; Lumando, Evelyn B.; Balicoco, Jhon Rey M.; Delima, Sheryl D. (Journal of Higher Education and Academic Advancement, 2024)
A study was conducted on the second grade non-readers in Toledo City's division. Eight pupils comprised up the cases. Three of them were Pantawid Pampamilyang Pilipino (4Ps) participants and they all came from low-income homes. The standard Philippine Informal Reading Inventory, a technique for evaluating the students' reading ability, was used to identify the extent of their reading difficulties. Pronunciation, omission, identification, mispronunciation, substitution, recognition, and non-readers were among the reading difficulties. Peer mentoring as a reading remediation and instruction eliminates non-readers and other reading problems in the school, according to a theory that the researcher developed as a result of the improvements made by the mentees. A peer mentoring plan was also developed by the researchers as assistance to the reading remediation program of the elementary school. In order to thoroughly examine the disability, look for correlations of the disability, and discover the underlying reasons of the reading handicap, it is imperative that all students from Grade Two up to Grade Six be diagnosed through a complete analysis of causality.